Unformatted text preview: dx = aUydt and dy = Udt Integrating the equation for y , we find y = y o + Ut where we assume y = y o at t = 0 . Substituting for y , the equation for x becomes dx = aU ( y o + Ut ) dt = ⇒ x = x o + aUt w y o + 1 2 Ut W Thus, the particle location is given by x = x o + aUt w y o + 1 2 Ut W and y = y o + Ut Therefore, the Lagrangian description of this flow is r = } x o + aUt w y o + 1 2 Ut W] i + [ y o + Ut ] j...
View Full Document
This note was uploaded on 02/09/2012 for the course AME 309 taught by Professor Phares during the Spring '06 term at USC.
- Spring '06